The genome sequence of a lauxanid fly, Meiosimyza decipiens (Loew, 1847) [version 1; peer review: 2 approved, 1 approved with reservations] - James McCulloch; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a male Meiosimyza decipiens (fly; Arthropoda; Insecta; Diptera; Lauxaniidae). The genome sequence has a total length of 436.39 megabases. Most of the assembly (99.68%) is scaffolded into 6 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 16.39 kilobases in length.